The Payments Systems Reforms and Monetary Policy in Emerging Market Economies in Central and Eastern Europe. (IMF Working Papers; Working Paper ;, 1994)
The paper discusses the interrelationships between payments system reform and monetary policy implementation in selected countries in Central and Eastern Europe. The reforms in the payments system are viewed as closely interrelated with the development of money and foreign exchange markets and the instruments of monetary policy used by the central banks. Large and variable float balances created special challenges. The paper shows that while departing from very similar origins, there were significant variations in experiences of the countries studied in transforming their payments systems after the start of the reforms towards a market economy, from which certain lessons can be drawn.